Assessment of background ionizing radiation exposure levels in industrial buildings in Nnewi, Anambra State, Nigeria - Chiegwu, Hyacienth U.; Onyeka, Jonathan O.; Ugwuanyi, Daniel C.; Odunk, Daniel D.; Ogolodom, Michael P.; Mbaba, Awajimijan N.; Nwodo, Victor K.; Ezechukwu, Uchenna N. (International Journal of Research in Medical Sciences, 2022)
Background: Increased exposure from background radiations and the attendant health effects have in recent times drawn the attention of researchers. This study aimed to assess the indoor and outdoor background radiation levels in selected offices/industrial buildings in Nnewi, Anambra State, Nigeria. Methods: Forty buildings in the four villages of Nnewi were surveyed using a calibrated international medicom CRM 100 radiation monitor. Radiation readings were obtained in counts per minute and converted to micro-sieverts per hour (µSv h-1). The indoor annual effective dose rate (IAEDR), outdoor annual effective dose rate, excess lifetime cancer risk, and organ doses were calculated using recommended occupancy and conversion factors. Results: The mean IAEDR and OAEDR were respectively 0.8060±0.056 mSv y-1 and 0.2281±0.020 mSv y-1 with estimated ELCR of 2.822x10-3 and 0. 799x10-3 respectively. The testes received the highest dose (0.843 mSv y-1) followed by bone marrow (0.710 mSv y-1). Conclusions: The study revealed that the mean background radiation exposures in and outside offices in Nnewi, Anambra State were below the UNSCEAR and ICRP recommended doses for the general public.